2015
DOI: 10.1016/j.conbuildmat.2015.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the structure and flexural properties of Moso, Guadua and Tre Gai bamboo

Abstract: Bamboo is an underutilized resource widely available in countries with rapidly developing economies. Structural bamboo products, analogous to wood products, allow flexibility in the shape and dimensions of bamboo structural members. Here, the ultrastructure, microstructure, cell wall properties and flexural properties of three species of bamboo (Moso, Guadua and Tre Gai) are compared. At a given density, the axial modulus of elasticity of Guadua is higher than that of Moso or Tre Gai, which are similar; ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 36 publications
(48 reference statements)
4
47
0
Order By: Relevance
“…If the relative differences are small, however, the methods will not show the same differences in relative crystallinity. This negative cc cellulose/glucose content, NMR nuclear magnetic resonance, PL plant material, WD unprocessed wood material, PP processed pulp, MCC microcrystalline cellulose, PT perpendicular transmission, ST symmetrical transmission, SR symmetrical reflection a Dixon et al (2015) b Borrega et al (2015) c Parviainen et al (2014) d Testova et al (2014) e Leppänen et al (2009) f Approximate cellulose content g Jeoh et al (2007) Cellulose (2016) As shown in the result section, differences in sample crystallinity values obtained with the Segal method can also be due to differences in crystallite sizes. A positive correlation between the crystallite size and the Segal crystallinity value has also been shown by Nam et al (2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the relative differences are small, however, the methods will not show the same differences in relative crystallinity. This negative cc cellulose/glucose content, NMR nuclear magnetic resonance, PL plant material, WD unprocessed wood material, PP processed pulp, MCC microcrystalline cellulose, PT perpendicular transmission, ST symmetrical transmission, SR symmetrical reflection a Dixon et al (2015) b Borrega et al (2015) c Parviainen et al (2014) d Testova et al (2014) e Leppänen et al (2009) f Approximate cellulose content g Jeoh et al (2007) Cellulose (2016) As shown in the result section, differences in sample crystallinity values obtained with the Segal method can also be due to differences in crystallite sizes. A positive correlation between the crystallite size and the Segal crystallinity value has also been shown by Nam et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Samples of low-and medium-density balsa (86 and 159 g/cm 3 , respectively) , spruce-pine sulphite pulp and nata de coco (Parviainen et al 2014), birch pulp (Testova et al 2014), bamboo (Dixon et al 2015), and MCC from birch sulphite, poplar kraft and cotton linters (Leppänen et al 2009) were analyzed. The published properties of these samples are summarized in Online Resource 1.…”
Section: Samplesmentioning
confidence: 99%
“…These exposures were averaged over a time period of 60 s to improve signal-to-noise ratio. Each averaged exposure was corrected as described in Dixon et al (2015). The ambient relative humidity was between 19.2 and 31.3% and the ambient temperature was between 28.7 and 29.3 C during the measurements.…”
Section: Wide-angle X-ray Scattering (Waxs)mentioning
confidence: 99%
“…The modulus of rupture showed a better relationship with the area damaged by the winds per clone, followed by the modulus of elasticity and compression parallel to grain, respectively. The modulus of rupture showed a relationship with the cell wall fraction and basic density (Longui et al, 2014;Dixon et al, 2015), parameters that also showed high correlation with the area damaged by the winds per clone. This showed how wind resistance was the result of a set of wood characteristics.…”
Section: Resultsmentioning
confidence: 99%